ONT sequencing identifies a high prevalence of crt sensitive, triple mutant dhfr and single mutant dhps parasites within an ANC population in Nigeria - Adegbola, Adebanjo Jonathan; Ndwiga, Leonard; Wamae, Kevin; Osoti, Victor; Bolaji, Oluseye Oladotun; Bejon, Philip; Ochola-Oyier, Lynette Isabella (Frontiers in Genetics, 2024)
Malaria in pregnancy is a major public health issue, particularly among vulnerable populations in malaria-endemic sub-Saharan African countries. To mitigate its risks, WHO recommends sulphadoxine-pyrimethamine (SP) for chemoprevention and artemisinin-based combination therapy (ACT) to treat uncomplicated Plasmodium falciparum malaria. These interventions have helped to alleviate the risk associated with malaria in pregnancy; however, in the context of the emergence of SP-and ACT-resistant P. falciparum, maintained efficacy is under threat. Molecular surveillance is a reliable tool to monitor the emergence of resistance where molecular markers are known. Thus, the objective of the study was to use a multiplexed amplicon Oxford Nanopore sequencing approach to assess the molecular markers for antimalarial resistance among pregnant women in Nigeria.Method: Dried blood spots (DBS) were collected from pregnant women who received IPTp-SP at the enrollment and follow-up visits. P. falciparum genomic DNA was extracted by the Chelex® method and Pf18S qPCR was used to detect parasite DNA in each sample. With nested PCR assays, fragments of Pfdhps, Pfdhfr, Pfmdr1, Pfcrt, Pfk13 and Pfama1 genes were amplified and multiplexed amplicon-based sequencing was conducted on the minION Oxford Nanopore Technology.Result: In total, 251 pregnant women were enrolled in the study and 457 DBS samples were collected. P. falciparum genomic DNA was detected in 12% (56/457) of the samples, 31 at baseline and the remaining during the follow-up visits. Pfama1, pfk13, Pfdhps, Pfdhfr, Pfmdr1 and Pfcrt were successfully sequenced in a single run. Notably, k13 artemisinin resistance mutations were